2018
DOI: 10.15252/embj.201797840
|View full text |Cite
|
Sign up to set email alerts
|

The WD 40 domain of ATG 16L1 is required for its non‐canonical role in lipidation of LC 3 at single membranes

Abstract: A hallmark of macroautophagy is the covalent lipidation of LC3 and insertion into the double‐membrane phagophore, which is driven by the ATG16L1/ATG5‐ATG12 complex. In contrast, non‐canonical autophagy is a pathway through which LC3 is lipidated and inserted into single membranes, particularly endolysosomal vacuoles during cell engulfment events such as LC3‐associated phagocytosis. Factors controlling the targeting of ATG16L1 to phagophores are dispensable for non‐canonical autophagy, for which the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
238
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 225 publications
(247 citation statements)
references
References 45 publications
9
238
0
Order By: Relevance
“…Furthermore, we tested LC3 lipidation induced by carbonyl cyanide m-chlorophenylhydrazone (CCCP, 10 lM) treatment, shown to induce the selective degradation of mitochondria (Narendra et al, 2008), and similarly observed defective LC3 lipidation in ATG16L1 LD -expressing cells (Fig 5B). Consistent with previous results, these treatments required the activity of ATG16L1 WT to support LC3 lipidation (Fig 5D and E;Fletcher et al, 2018), whereas LC3 lipidation was strongly diminished in ATG16L1 LD -expressing cells. Given that noncanonical LC3 lipidation can occur on single membranes and requires the ATG5 complex but not additional upstream autophagy machinery, such as WIPI2 or the ULK1 complex, we further examined whether ATG16L1 LD could support LC3 lipidation during treatment with monensin, ammonium chloride (NH 4 Cl) or CCCP (100 lM), known to act as ionophores and/or lysosomotropic agents (Jacquin et al, 2017).…”
Section: Binding Of Atg16l1 To Lipids Is Required For Autophagysupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, we tested LC3 lipidation induced by carbonyl cyanide m-chlorophenylhydrazone (CCCP, 10 lM) treatment, shown to induce the selective degradation of mitochondria (Narendra et al, 2008), and similarly observed defective LC3 lipidation in ATG16L1 LD -expressing cells (Fig 5B). Consistent with previous results, these treatments required the activity of ATG16L1 WT to support LC3 lipidation (Fig 5D and E;Fletcher et al, 2018), whereas LC3 lipidation was strongly diminished in ATG16L1 LD -expressing cells. Given that noncanonical LC3 lipidation can occur on single membranes and requires the ATG5 complex but not additional upstream autophagy machinery, such as WIPI2 or the ULK1 complex, we further examined whether ATG16L1 LD could support LC3 lipidation during treatment with monensin, ammonium chloride (NH 4 Cl) or CCCP (100 lM), known to act as ionophores and/or lysosomotropic agents (Jacquin et al, 2017).…”
Section: Binding Of Atg16l1 To Lipids Is Required For Autophagysupporting
confidence: 92%
“…Interestingly, a recent study shows that the recruitment of WIPI2-to PI3P-positive recycling endosomes requires both its lipid and protein interactions with PI3P and RAB11A, respectively (Puri et al, 2018). Furthermore, ATG16L1-dependent lipidation of LC3 on single membranes, for example during treatment with ionophores and lysosomotropic agents, has been shown to occur independently of FIP200, WIPI2 and PI3P (Florey et al, 2015;Fletcher et al, 2018). Furthermore, ATG16L1-dependent lipidation of LC3 on single membranes, for example during treatment with ionophores and lysosomotropic agents, has been shown to occur independently of FIP200, WIPI2 and PI3P (Florey et al, 2015;Fletcher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work shows that autophagy and phagocytosis can be linked by non-canonical autophagy. This is best characterized in 10 phagocytic cells where LC3 associated phagocytosis (LAP) is activated by Toll-like receptor signaling resulting in recruitment of autophagy marker protein LC3 to the phagosome membrane to enhance phagosome maturation [1][2][3][4][5] . In non-phagocytes a similar non-canonical pathway recruits LC3 to endo-lysosome compartments during the uptake of particulate material such as apoptotic cells and aggregated β-amyloid and 15 following membrane damage during pathogen entry or osmotic imbalance induced by lysosomotropic drugs 6,7 8-10 .…”
Section: Resultsmentioning
confidence: 99%
“…This prompted us to generate a mouse lacking the WD domain of ATG16L1 to study the role 10 played by non-canonical autophagy in vivo 21 . The mouse model (WD [Atg16L1 wd/wd ]) carries a stop codon after the coiled coil domain which removes amino acid residues at 266 and 319 in the linker region and conserved phenylalanine residues at positions 467 and 490 in the WD domain required for lipid binding of ATG16L1 and subsequent recruitment of ATG5-ATG12 to endo-lysosome membranes 2,22 . As a consequence the 15 mice are unable to conjugate LC3 to endo-lysosome membrane compartments 21 , but the mutation preserves the N-terminal ATG5-binding domain and glutamates at positions 226 and 230 in the CCD of ATG16L1 that are required for WIPI2 binding and autophagy 23 .…”
Section: Resultsmentioning
confidence: 99%